Linguistic formations in the novel of Oissini Alaraj « The jumlokia of Arabia ». (Numerus academy review, 2026)
The novel is a literary race that is open to the issues and existential problems ofthe world, and this openness of the novel stems from its ability to contain other literaryraces, It permeates the narrative enrich it in its various dictionaries, from a linguistic pointof view, the interest in multilingualism has become evident in the multiplicity of voices that are spoken, the text is no longer monopolized or settled on a single language, but isopen to social languages to rid the narrative language of stereotyping and abstraction.In this article, we try to identify the various linguistic formations in the novel"Jumlokia Arabia", considering Laraj as a model for the Algerian novelist whose writings do not settle in one form